High contrast gasochromism of wet processable thin film with chromic and catalytic nanoparticles. Issue 17 (19th April 2018) - Hu, Chih-Wei; Yamada, Yasusei; Yoshimura, Kazuki; Takahashi, Akira; Watanabe, Hiroshi; Tajima, Kazuki; Kawamoto, Tohru
Abstract : We demonstrate high contrast gasochromism in a thin film produced by combining chromic Prussian blue nanoparticles and catalytic platinum nanoparticles, applied by sequential wet-coating onto a substrate. Abstract : We demonstrate high contrast gasochromism in a thin film produced by combining chromic Prussian blue nanoparticles and catalytic platinum nanoparticles, applied by sequential wet-coating onto a substrate. The contrast ratio at 700 nm reaches 80. The cycle stability exceeds 200 cycles. H2 with low concentration (4%-H2 ) and air can drive the change of colour between blue and colourless. We also reveal via X-ray diffraction, Fourier-transform IR spectroscopy, and investigation of the redox potential of a series of metal-substituted Prussian blue analogues, that bleaching results from the reduction of Prussian blue nanoparticles by protons generated using platinum nanoparticles.